The care and handling of roses with thorns - Dilloway, Margaret (G. P. Putnam's Sons, 2012)
Thirty-six-year-old biology teacher Gal Garner's regimented life will never be the same after her estranged sister's teenage daughter Riley arrives one afternoon unannounced.